Understanding olfaction and emotions and the moderating role of individual differences - Lin, Meng-Hsien (Jenny) and Cross, Samantha N.N. and Childers, Terry L. (European Journal of Marketing, 2018)
Purpose The purpose of this paper is to explore the mediating role of emotions in processing scent information in consumer research, using event-related potential (ERP)-based neuroscience methods, while considering individual differences in sense of smell. Design/methodology/approach Prior research on olfaction and emotions in marketing has revealed mixed findings on the relationship between olfaction and emotion. The authors review earlier studies and present a neuroscience experiment demonstrating the benefits of ERP methods in studying the automatic processing of emotions. Findings Results demonstrate how emotional processes occurring within 1s of stimulus exposure differ across individuals with varying olfactory abilities. Findings reveal an automatic suppression mechanism for individuals sensitive to smell. Research limitations/implications Scent-induced emotions demonstrated through the use of ERP-based methods provide insights for understanding automatic emotional processes and reactions to ambient scents by consumers in the marketplace. Practical implications Findings show an automatic suppression of emotions triggered by scent in individuals sensitive to smell. Marketers and retailers should consider such reactions when evaluating the use of olfactory stimuli in promotional and retail strategies. Originality/value The authors review past literature and provide an explanation for the disparate findings in the olfaction–emotion linkage, by studying individual differences in response to scent in the marketplace. This is one of the first papers in marketing to introduce the application of ERP in studying consumer-relevant behavior and provide technical and marketing-specific considerations for both academic and market researchers.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTEwOC9lam0tMDUtMjAxNS0wMjg0